Metabolic Adaptations in Plants During Abiotic Stress - Ramakrishna, Akula; Singh Gill, Sarvajeet; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Key features: Serves as a cutting-edge resource for researchers and students who are studying plant abiotic stress tolerance and crop improvement through metabolic adaptations Presents the latest trends and developments in the field of metabolic engineering and abiotic stress tolerance Addresses the adaptation of plants to climatic changes Gives special attention to emerging topics such as the role of secondary metabolites, small RNA mediated regulation and signaling molecule responses to stresses Provides extensive references that serve as entry points for further research Metabolic Adaptations in Plants during Abiotic Stress covers a topic of past, present and future interest for both scientists and policy makers as the global challenge of climate change is addressed. Understanding the mechanisms of plant adaptation to environmental stresses can provide the necessary tools needed to take action to protect them, and hence ourselves. This book brings together recent findings about metabolic adaptations during abiotic stress and in diverse areas of plant adaptation. It covers not only the published results, but also introduces new concepts and findings to offer original views on the perspectives and challenges in this field.
Contents -- Foreword.....xi -- Acknowledgments....... xiii -- Editors.......xv -- Contributors. xvii -- Section I Abiotic Stress Management and Its Impact on Plants -- 1. Effects of Different Abiotic Stresses on Primary Metabolism....3 -- Belen Colavolpe, Fabiana Espasandin, Juan Manuel Vilas, Santiago Maiale, Pedro Sansberro, and Oscar A. Ruiz -- 2. Metabolic Adaptation and Allocation of Metabolites to Phloem Transport and Regulation Under Stress21 -- Kathryn Dumschott, Andrew Merchant, and Millicent Smith -- 3. Mechanism of Salt Stress Tolerance and Pathways in Crop Plants.........27 -- Manu Kumar and Mahipal Singh Kesawat -- 4. Recent Advances on the Modulatory Role of ATPases toward Salt Tolerance in Plants....45 -- Soumya Mukherjee -- 5. Physiological and Phenological Responses of Crop Plants under Heat Stress55 -- Allah Ditta -- 6. Biochemical and Molecular Mechanisms of HighTemperature Stress in Crop Plants....65 -- Gurpreet Kaur, Bavita Asthir, and N.S. Bains -- 7. Profiles of Antioxidant Isoenzymes and Physiological Behavior of Tomato Exposed to NaCl Stress and Treated -- with Salicylic Acid...73 -- Salma Wasti, Nizar Dhaoui, Ibtissem Medyouni, Hajer Mimouni, Hela Ben Ahmed, and Abdellah Chalh -- 8. Toxicity of Heavy Metal and Its Mitigation Strategies through Application of Nutrients, Hormones, -- and Metabolites.....81 -- Rachana Singh, Parul Parihar, Anita Singh, and Sheo Mohan Prasad -- 9. Regulation of Pesticide Stress on Metabolic Activities of Plant..99 -- Santwana Tiwari, Anita Singh, and Sheo Mohan Prasad -- 10. Oxidative Stress and Its Management in Plants During Abiotic Stress....111 -- P. Faseela, A.K. Sinisha, T.T. Dhanya Thomas, and Jos T. Puthur -- 11. Plant Genome Response Related to Phenylpropanoid Induction under Abiotic Stresses..127 -- Ariel D. Arencibia -- 12. Metabolic Control of Seed Dormancy and Germination: New Approaches Based in Seed Shape -- Quantification in Desert Plants...137 -- Emilio Cervantes, Jos Javier Martn Gmez, and Ezzeddine Saadaoui -- 13. Plant Ionomics: An Important Component of Functional Biology........147 -- Anita Mann, Sangeeta Singh, Gurpreet, Ashwani Kumar, Pooja Sujit Kumar, and Bhumesh Kumar -- Section II Role of Major Plant Metabolites During Abiotic Stress Management -- 14. Role of Glutamate-Derived Amino Acids under Stress Conditions: The Case of Glutamine and Proline157 -- Marco Biancucci, Roberto Mattioli, Adra Mouellef, Nadia Ykhlef, and Maurizio Trovato -- 15. Role of Glycinebetaine and Trehalose as Osmoregulators During Abiotic Stress Tolerance in Plants...171 -- Mona G. Dawood and Mohamed E. El-Awadi -- 16. Polyamine Metabolism and Abiotic Stress Tolerance in Plants.191 -- Rubn Alczar and Antonio F. Tiburcio -- 17. Plant Glycine-Rich Proteins and Abiotic Stress Tolerance.....203 -- Juan Francisco Jimnez-Bremont, Maria Azucena Ortega-Amaro, Itzell Eurdice Hernndez-Snchez, Alma Laura -- Rodriguez-Pia, and Israel Maruri-Lopez -- 18. Compatible Solutes and Abiotic Stress Tolerance in Plants....213 -- Vinay Kumar, Tushar Khare, Samrin Shaikh, and Shabir H. Wani -- 19. Protective Role of Indoleamines (Serotonin and Melatonin) During Abiotic Stress in Plants..........221 -- Ramakrishna Akula, Sarvajeet Singh Gill, and G.A. Ravishankar -- 20. Flavonoid Accumulation as Adaptation Response in Plants during Abiotic Stresses.....229 -- Rubal, Ashok Dhawan, and Vinay Kumar -- 21. The Role of Gamma Aminobutyric Acid (GABA) During Abiotic Stress in Plants.......239 -- Paramita Bhattacharjee, Sasanka Chakraborti, Soumi Chakraborty, and Kaninika Paul -- Section III Role of Specialized Proteins During Abiotic Stress Management -- 22. MicroRNAs: Emerging Roles in Abiotic Stresses and Metabolic Processes.251 -- Susana S. Arajo, Carolina Gomes, Jorge A.P. Pavia, Alma Balestrazzi, and Anca Macovei -- 23. Current Understanding of Regulation of GBF3 Under Abiotic and Biotic Stresses and Its Potential Role in -- Combined Stress Tolerance......267 -- Sandeep Kumar Dixit, Aarti Gupta, and Muthappa Senthil-Kumar -- 24. microRNAs: Key Modulators of Drought Stress Responses in Plants.....273 -- A. Thilagavathy, Kavya Naik, and V.R. Devaraj -- 25. Proteomics of Salinity Stress: Opportunities and Challenges..285 -- Shweta Jha -- Section IV Role of Signaling Molecules Under Abiotic Stress Management -- 26. Signaling Molecules and Their Involvement in Abiotic and Biotic Stress Response Crosstalk in Plants.295 -- V.R. Devaraj and R.D. Myrene -- 27. Current Understanding of the Role of Jasmonic Acid During Photoinhibition in Plants..311 -- Ruquia Mushtaq, Sarvajeet S. Gill, Shruti Kaushik, Anil K. Singh, Akula Ramakrishna, and Geetika Sirhindi -- 28. Current Scenario of NO (S-Nitrosylation) in Cold Stress......331 -- Yaiphabi Sougrakpam, Priyanka Babuta, and Renu Deswal -- 29. Physiological Roles of Brassinosteroids in Conferring Temperature and Salt Stress Tolerance in Plants341 -- Sirhindi Geetika, Bhardwaj Renu, Kumar Manish, Kumar Sandeep, Dogra Neha, Sekhon Harpreet, -- Kaushik Shruti and Madaan Isha -- Section V Biotechnological Applications to Improve the Plant -- Metabolic Pathways Towards Better Adaptations -- 30. Genetic Engineering Approaches for Abiotic Stress Tolerance in Broccoli: Recent Progress..........363 -- Pankaj Kumar, Ajay Kumar Thakur, and Dinesh Kumar Srivastava -- 31. Impact of Abiotic Stresses on Metabolic Adaptation in Opium Poppy (Papaver somniferum L.)......371 -- Ankesh Pandey, S. N. Jena, and Sudhir Shukla -- 32. In Vitro Selection and Genetic Engineering for Abiotic Stress Tolerant Plants and Underlying Mechanism.........383 -- Srinath Rao and H. Sandhya -- 33. Plant-environment Interaction: Influence of Abiotic Stress on Plant Essential Oil Yield and Quality...391 -- Marine Hussain, Barbi Gogoi, Babita Joshi, Bitupon Borah, Lucy Lalthafamkimi and B.S. Bhau -- 34. Differences in Adaptation to Water Stress in Stress Sensitive and Resistant Varieties of Kabuli and Desi Type -- Chickpea403 -- Nadia Fatnassi, Ralph Horres, Natasa Cerekovic, Angelo Santino, and Palmiro Poltronieri.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Life Sciences / Biology / Molecular Biology; TECHNOLOGY & ENGINEERING / Agriculture / General; Cellular processes of plants; Climate change and vegetation; Molecular mechanisms of plants; Photosynthesis; Protein synthesis; Signaling molecules; Plants -- Adaptation; Plants -- Effect of stress on; Plants -- Metabolism; Electronic books